General Services Administration proposes to regulate smoking areas in GSA-controlled buildings. Comments on the proposal are due on or before July 21, 1986 (Tufts Archival Research Center, 2007)
Federal Relations Report on General Services Administration smoking regulations. Recognizes rights of smokers. Aknowledges potential harmful effects of secondhand smoke. Stipulates that no smoking is allowed in general office space, auditoriums, or elevators. Provides guidelines for enforcement policies and notification.